The moon over stars - Aston, Dianna Hutts (The Penguin Group, 2008)
On her family's farm in the town of Star, eight-year-old Mae eagerly follows the progress of the 1969 Apollo 11 flights and moon landing and dreams that she might one day be an astronaut, too